Cross-sectional variation in the stock market response to accounting earnings announcements - Easton, Peter D.; Zmijewski, Mark E. (Journal of Accounting and Economics, 1989)
Studies of the information content of accounting earnings typically assume earnings response coefficients do not vary across firms. Valuation models relating earnings to security prices, however, predict that earnings response coefficients are positively associated with revision coefficients (coefficients relating current earnings to future earnings) and negatively associated with expected rates of return. A random coefficient regression model provides evidence consistent with these predictions. This evidence has implications for interpreting multiple regression models that relate abnormal returns to unexpected earnings and other information variables.